Calibrating Partial Factors – Methodology, Input Data and Case Study of Steel Structures: Methodology, Input Data and Case Study of Steel Structures - Nadolski, Vitali; Rózsás, Árpád; Sýkora, Miroslav (Periodica Polytechnica Civil Engineering, 2019)
Partial factors are commonly based on expert judgements and on calibration to previous design formats. This inevitably results in unbalanced structural reliability for different types of construction materials, loads and limit states. Probabilistic calibration makes it possible to account for plentiful requirements on structural performance, environmental conditions, production and execution quality etc. In the light of ongoing revisions of Eurocodes and the development of National Annexes, the study overviews the methodology of probabilistic calibration, provides input data for models of basic variables and illustrates the application by a case study. It appears that the partial factors recommended in the current standards provide for a lower reliability level than that indicated in EN 1990. Different values should be considered for the partial factors for imposed, wind and snow loads, appreciating the distinct nature of uncertainties in their load effects.